1995
DOI: 10.7863/jum.1995.14.6.435
|View full text |Cite
|
Sign up to set email alerts
|

Doppler sonography of the inferior mesenteric artery: a preliminary study.

Abstract: The purposes of this study were to look for the inferior mesenteric artery in patients undergoing abdominal sonography, to determine in what percentage of patients it is visible, and to characterize Doppler flow patterns of the inferior mesenteric artery in fasting patients without intestinal vascular disease. The inferior mesenteric artery was sought in 100 consecutive fasting adults (mean age, 54 years; 63 women, 37 men), as follows: the infrarenal aorta was scanned in a transverse plane; the origin of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 3 publications
2
11
0
Order By: Relevance
“…The first report of this type regarding the IMA was published by our group following a preliminary study of normal and pathological cases [8]. These data have been confirmed by others in a more recent study of the same type [18].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The first report of this type regarding the IMA was published by our group following a preliminary study of normal and pathological cases [8]. These data have been confirmed by others in a more recent study of the same type [18].…”
Section: Discussionsupporting
confidence: 74%
“…Besides reporting the results relative to a larger population, the present study differs from the previously published papers [8,18] in that the sonographic and Graph showing estimated flow volumes (range and SD) for the IMA with respect to patient age (õ50 years or ¢50 years). The difference between the two age groups is statistically significant (p Å 0.01).…”
Section: Discussionmentioning
confidence: 47%
“…On the other hand, the normal spectral patterns of the superior and inferior mesen teric arteries in the fasting state are similar to the higher-resistancevesselsin the periphery. The mean RI in the normal superior mesen teric artery is about 0.85 ± 0.04 [7,111 and is lower than the mean RI of the inferior mesen teric artery. According to these results, we suggest that the inferior mesenteric artery has the highest RI of the abdominal visceral yes sels.…”
Section: Group3: Occlusion Ofthe Aortamentioning
confidence: 70%
“…Mirk [6) The low velocity of end-diastolic flow causes the RI of the inferior mesenteric artery to be considerably high. In the study by Do nys et al [7], the mean RI in healthy individ uals is 0.959 ± 0.045. In our study, this value was 0.89 ±0.06 in the control group.…”
Section: Group3: Occlusion Ofthe Aortamentioning
confidence: 90%
“…US exploration of the inferior mesenteric artery is more difficult because of its small size and position next to the loop of the small intestine. The first study on color Doppler US evaluation of the inferior mesenteric artery was reported by Mirk et al [6], who published data which were reconfirmed in later studies [15,16].…”
Section: Discussionmentioning
confidence: 96%